2023
DOI: 10.1001/jama.2023.15694
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes After Minimally Invasive Surfactant Therapy in Preterm Infants

Abstract: ImportanceThe long-term effects of surfactant administration via a thin catheter (minimally invasive surfactant therapy [MIST]) in preterm infants with respiratory distress syndrome remain to be definitively clarified.ObjectiveTo examine the effect of MIST on death or neurodevelopmental disability (NDD) at 2 years’ corrected age.Design, Setting, and ParticipantsFollow-up study of a randomized clinical trial with blinding of clinicians and outcome assessors conducted in 33 tertiary-level neonatal intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the Discussion section of this study, the authors mentioned that the difference in the number of laryngoscopy procedures between the MIST group and the control group did not result in neurodevelopmental disability differences. However, the calculation method treating the Hobart method and traditional intubation as the same in terms of frequency does not align with clinical experience, given that the Hobart method results in shorter procedure times and less stress for the infants.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In the Discussion section of this study, the authors mentioned that the difference in the number of laryngoscopy procedures between the MIST group and the control group did not result in neurodevelopmental disability differences. However, the calculation method treating the Hobart method and traditional intubation as the same in terms of frequency does not align with clinical experience, given that the Hobart method results in shorter procedure times and less stress for the infants.…”
mentioning
confidence: 89%
“…To the Editor A recent 2-year follow-up study of the OPTIMIST-A randomized clinical trial of preterm infants with respiratory distress syndrome found that MIST did not reduce the incidence of death or severe neurodevelopmental disability by 2 years of age. We have several concerns about the interpretation of this study’s results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor A recent 2-year follow-up study compared the effect of minimally invasive surfactant therapy (MIST) vs control (placebo) on neurodevelopment disability and death at 2 years’ corrected age.…”
mentioning
confidence: 99%
“…In Reply Regarding our recent article reporting the 2-year outcomes after MIST in preterm infants, Drs Liu and Shi inquire why the BSID-IV was not used for assessment of neurodevelopmental disability. The explanation is that the BSID-IV was published in 2019, which was 5 years after the follow-up assessments were commenced for our study.…”
mentioning
confidence: 99%